LOYALITAS PELANGGAN TOKO AGNA JAYA PASAR LEGI DITINJAU DARI PELAYANAN, KETERIKATAN EMOSIONAL DAN GETHOK TULAR - Yusuf Roni; Supawi Pawenang; Ratna Damayanti (JURNAL ILMIAH EDUNOMIKA, 2020)
Customer loyalty is the state of the customer begins to have a positive attitude to a brand, so that it raises a commitment to brand, and intends to make a repeat purchase in the future. This studyi aims to determine the effecti of service, emotional attachment and gethok tular on customer loyalty in Agna Jaya stores both partially and simultaneously. The population of this study is traditional market trades who are customers of Agna Jaya stores and take a sample of 40 respondents. The analysis technique in this study uses the method of multiple linear regresion analysis. The results showed that service, emotional attachment and gethok tular simultaneously influence customer loyalty. Partially service, emotional attachment and gethok tular havei a significanti effect on customeri loyalty. Keywords: Customer loyalty, iservice, emotional attachment, gethok tular